2007
DOI: 10.1101/lm.461407
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 receptors regulate protein synthesis-dependent long-term recognition memory via extracellular signal-regulated kinase 1/2 in the prefrontal cortex

Abstract: Several lines of evidence suggest that extracellular signal-regulated kinase1/2 (ERK1/2) and dopaminergic system is involved in learning and memory. However, it remains to be determined if the dopaminergic system and ERK1/2 pathway contribute to cognitive function in the prefrontal cortex (PFC). The amount of phosphorylated ERK1/2 was increased in the PFC immediately after exposure to novel objects in the training session of the novel object recognition test. An inhibitor of ERK kinase impaired long-term recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
114
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 174 publications
(136 citation statements)
references
References 77 publications
15
114
1
5
Order By: Relevance
“…Previously it was shown that behavior in this test depends on functions of prefrontal cortex (Nagai et al, 2007), however the obtained data does not allow us to state that recognition memory impairment in this group was due to changes in frontal cortex. GFAP level is considered as an indicator of tissue damage after irradiation.…”
Section: Discussioncontrasting
confidence: 38%
“…Previously it was shown that behavior in this test depends on functions of prefrontal cortex (Nagai et al, 2007), however the obtained data does not allow us to state that recognition memory impairment in this group was due to changes in frontal cortex. GFAP level is considered as an indicator of tissue damage after irradiation.…”
Section: Discussioncontrasting
confidence: 38%
“…These findings also suggest that FMRP might control shared signaling molecules that are key players to regulate neurotransmitter-mediated signaling and protein synthesis. The two major pathways regulating neurotransmitter-induced protein synthesis in neurons are the ERK1/2 and the PI3K/mTOR (mammalian target of rapamycin) pathways (Banko et al, 2006;Nagai et al, 2007;Schicknick et al, 2008;Santos et al, 2010;Zhou et al, 2010). Both pathways also play crucial roles for intracellular signaling, and many of the above discussed dysregulated neurotransmitter-dependent signaling mechanisms in FXS are regulated or mediated via ERK1/2 and/or PI3K signaling (Figure 1).…”
Section: Targeting Downstream Signaling Molecules In Fxsmentioning
confidence: 99%
“…As mentioned under Introduction, diminished dopaminergic and noradrenergic function in the cortex and HIP have been implicated in the pathophysiology of cognitive impairment, negative symptoms, and perhaps depression in patients with schizophrenia (Meltzer and McGurk, 1999;Millan, 2006;Juckel et al, 2006). Recent studies have clearly demonstrated the importance of increased cortical D 1 receptor stimulation for specific types of memory, including working memory and social memory (Castner and Williams, 2007;Nagai et al, 2007), possibly by increasing the activity of pyramidal neurons, modulation of glutamate NMDA receptor signaling at critical nodes within local circuits and distributed networks (Castner and Williams, 2007), fine tuning GABAergic interneurons (Kroner et al, 2007), and enhancing the release of cortical ACh (Di Cara et al, 2007). Thus, these effects on the efflux of cortical DA and NE may be clinically relevant to the treatment of schizophrenia (Ichikawa et al, 2001;Meltzer et al, 2003;Arnsten and Li, 2005), as well as to the ability of these same agents, in combination with at least some antidepressant drugs, to be effective in patients with major depression who fail to respond to antidepressant drug treatment alone (Shelton et al, 2001).…”
Section: Da Effluxmentioning
confidence: 99%